The distribution and magnitude of subglacial erosion on millennial timescales at Engabreen, Norway - Cari Rand; Brent M. Goehring (Annals of Glaciology, 2019)
We quantify the magnitude of millennial-scale glacial erosion at Engabreen, a temperate glacier in coastal northern Norway, using the in situ cosmogenic nuclides carbon-14 (14C) and beryllium-10 (10Be) in bedrock exposed recently by glacial retreat. Nuclide concentrations show no dependence on distance down or across the valley. As such, resulting Holocene erosion depths along two transects perpendicular to glacier flow are highly variable with no systematic distribution, ranging from 0.10 to 2.95 m. We observed 14C–10Be ratios elevated above the production ratio in samples of abraded bedrock, which is counter to the expectation for surfaces covered during the Holocene and exposed only recently. Muon reactions produce nuclides at greater depths than do spallation reactions and 14C at production rates at higher than those of 10Be, resulting in 14C–10Be ratios that increase with depth. Therefore, elevated 14C–10Be ratios indicate that sampled sites were deeply plucked during recent cover, the Little Ice Age in this case, and then rapidly abraded prior to retreat. Our results suggest that, while glacial erosion can generate a u-shaped valley profile over long periods of time (e.g., 105–107 years), the discontinuous nature of glacial plucking produces spatially variable patterns of erosion over shorter millennial timescales.